The effect of different dietary levels of DL-methionine and DL-hydroxy analogue on the antioxidant status of young turkeys infected with the haemorrhagic enteritis virus - Jan Jankowski (BMC Veterinary Research, 2018)
Abstract Background The results of experiments involving broiler chickens and turkeys indicate that increased dietary methionine (Met) levels may improve the antioxidant protection of tissues in fast-growing birds. This is an important consideration since viral infections induce oxidative stress. The aim of this study was to verify the hypothesis that turkey diets with increased Met content can suppress oxidation processes induced by infection caused by the haemorrhagic enteritis virus (HEV), and that the noted effect is determined by the chemical form of this amino acid: DL-methionine (DLM) or DL-hydroxy analogue of Met (MHA). Results Dietary Met content above 40% higher than the level recommended by the NRC (1994) intensified lipid peroxidation in the small intestine, leading to an increase in malondialdehyde (MDA) and lipid peroxide (LOOH) levels, but it also stimulated antioxidant mechanisms in the blood and liver of turkeys infected with HEV. In comparison with DLM, MHA contributed to more severe symptoms of oxidative stress, such as elevated MDA levels in the intestines, and a decrease in glutathione peroxidase (GPx) activity and ferric-reducing ability of plasma (FRAP). Conclusions In HEV-infected turkeys, diets with increased Met content did not exert a clear antioxidant effect, which was noted in uninfected birds. The prooxidant activity of Met observed in the small intestinal wall was suppressed in the blood and liver of turkeys, most likely due to intensified synthesis of uric acid and glutathione. In comparison with MHA, DLM had a more beneficial influence on the analysed parameters of the redox status in the small intestine, blood and liver of turkeys.